Science, belief and society : international perspectives on religion, non-religion and the public understanding of science - Jones, Stephen H., 1981-; Kaden, Tom; Catto, Rebecca; Davie, Grace (Policy Press scholarship online., 2019)
The relationship between science and belief has been a prominent subject of public debate for many years, covering everything from science communication, health and education to immigration and national values. Yet, sociological analysis of these subjects remains surprisingly scarce. This wide-ranging book critically reviews the ways in which religious and non-religious belief systems interact with scientific methods, traditions and theories. Contributors explore how, for some secularists, 'science' forms an important part of social identity. Others examine how many contemporary religious movements justify their beliefs by making a claim upon science. Moving beyond the traditional focus on the United States, the book shows how debates about science and belief are firmly embedded in political conflict, class, community and culture